Epistemologi Keilmuan Pesantren Pendekatan Multidisipliner - Iwan Kuswandi; Asmoni Asmoni (Universitas KH. A. Wahab Hasbullah Tambakberas Jombang, 2023)
This article has described the epistemology of science in education in the Tarbiyatul Muallimien al-Islamiyah (TMI) Al-Amien Prenduan Islamic boarding school curriculum. The conclusion of this research is that the educational curriculum at TMI used is a multidisciplinary approach with an interconnected model of scientific epistemology. From ethics, by cultivating morals through studying moral books, such as Ta'lim Mutaallim and Ihya' Ulum ad-Din, as well as teaching material that trains reasoning and logic such as Logic, Ushul Fiqh and Musthalah Hadith subject matter, and research and practical lessons writing scientific papers. To strengthen the field of aesthetics, students are provided with interest groups and Puspagatra media as a center for creativity and development of their talents and interests.